Utilization of Waste Palm Shells to a Shampoo that Absorbs Dirt on Hair and Evaluated the Physical Properties of The Best Shampoo - Uce Lestari; Faizar Farid (Demeter: Journal of Farming and Agriculture, 2023)
Greasy hair becomes a major problem to the health of the hair, one of which is dandruff. This is because greasy hair can facilitate the adhesion of dirt. Active charcoal of palm oil shell is activated charcoal having a pore diameter in the range of 1.76 to 1.84 nm and it has been proven that it has absorption ability 2 times higher than commercial activated carbon to absorb the oil in hair. Based on this, active charcoal derived from palm oil shells is processed into cosmetic products. One of the cosmetic products that can be used to overcome hair health problems is shampoo. Shampoo formulations with a variety of concentrations of activated charcoal with palm shell with concentrations of 4% (FI), 8% (FII), 12% (FIII). Then the evaluation of shampoo's physical properties such as organoleptic, pH, homogeneity, viscosity, foam height, specific gravity, foam stability test and cycling test were carried out. In vitro test the effectiveness of the excess oil absorber by using a turbidimetric device. The comparison control used was Pantene shampoo as a positive control and the basis of the shampoo as a negative control. Showed that the higher the concentration of activated charcoal from the coconut shell, the better the ability to absorb excess oil with the largest NTU FIII value of 11,800. The formula that has good physical properties and is stable in storage and has good oil absorption ability is FIII